(untitled) (Nexo Revista Científica, 2018)
Trichoderma spp. is a polyvalent fungus, whose properties postulate it as a biological control agent of phytopathogens and a plant growth stimulant. Commonly isolated from decaying soils and wood, although isolates II2 and II8 (T viridae and T atroviridae) were isolated from historical monuments in Mexico City, DF. This work presents the characterization of the antagonism and promotion of plant growth of these isolates. These fungi were tested against phytopathogenic fungi Fusarium oxysporum and Macrophomina phaseolina, isolated from beans. The results show that the Trichoderma species studied do not modify their growth rate when grown in dual culture with the antagonists. The same result was obtained for F oxysporum when it grows against isolates II8 and II2. M phaseolina increases its rate of colony growth when it grows in the same Petri dish compared to the two species of Trichoderma. The antagonism by space competition was observed and mechanisms of antibiosis and hyperparasitism were not detected in these tests. When evaluating the potential agronomic use, stimulating the growth in sorghum plants through the height and biomass produced in the different treatments was determined that they do not have the capacity to stimulate the development of the plants. In contrast, inhibitory effects of the growth and development are generally observed on the treated plants. This may be due to the fact that these Trichoderma viridae y T atroviridae strains were isolated from historical monuments of the urban area of Mexico City.